Leveraging AWS Full Stack Development Platform for Scalable and Reliable Enterprise Applications - Anaswara Thekkan Rajan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud computing has become an essential innovation in the quickly changing digital change landscape, giving enterprises unprecedented operational flexibility and scale. The emergence of cloud computing has brought about a significant transformation in contemporary technological frameworks, with Amazon Web Services, also known as AWS, developing as a prominent cloud player. In order to realise AWS’s maximal potential and showcase its revolutionary advantages for both individuals and enterprises, the research delves into its subtleties. A method is shown for automating and expanding business application cloud installations using contemporary tools and techniques. Conventional infrastructure installations have lost ground to modern cloud-based alternatives for businesses. A detailed explanation is given of the AWS services utilised and the unique tasks they have in relation to the suggested design. To demonstrate the suggested architecture’s capacity to handle and absorb data, a stress test was carried out. Numerous commercial and open-source automating and scaling options are accessible. Performance, usability, and sustainability issues with automated the application’s deployment in the cloud exist. In earlier studies, we outlined specific standards for selecting a service that offers cloud storage and a method for growing cloud-based applications to thousands of users. Our objective is to provide a set of standards for selecting an appropriate scaling and automate strategy for applications used by businesses.